2018
DOI: 10.1021/acsomega.8b00778
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Basis of the Enhanced Interaction between Kinesin Spindle Protein Eg5 and STLC-type Inhibitors

Abstract: For a better understanding of protein–inhibitor interactions, we report structural, thermodynamic, and biological analyses of the interactions between S -trityl- l -cysteine (STLC) derivatives and the motor domain of kinesin spindle protein Eg5. Binding of STLC-type inhibitors to Eg5 was enthalpically driven and entropically unfavorable. The introduction of a para -methoxy substituent in one phenyl ring of STLC enhances its inhibitory activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To date, a large number of Eg5 inhibitors, such as STLC and PVZB1194, have been reported (Ogo et al, 2007;Matsuno et al, 2009). A large amount of structural information on Eg5 in complex with its inhibitors has also been reported (Yokoyama et al, 2015(Yokoyama et al, , 2018Myers & Collins, 2016). However, Eg5 inhibitors have not found clinical use because they target not only cancer cells but also other actively proliferating cells.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of Eg5 inhibitors, such as STLC and PVZB1194, have been reported (Ogo et al, 2007;Matsuno et al, 2009). A large amount of structural information on Eg5 in complex with its inhibitors has also been reported (Yokoyama et al, 2015(Yokoyama et al, , 2018Myers & Collins, 2016). However, Eg5 inhibitors have not found clinical use because they target not only cancer cells but also other actively proliferating cells.…”
Section: Introductionmentioning
confidence: 99%
“…There are well‐characterized KIF11 inhibitors that bind allosteric pockets of KIF11 and inhibit the release of ADP (Yokoyama et al , 2018 ) (Mayer et al , 1999 ; Tcherniuk et al , 2010 ; Venere et al , 2015 ; Wu et al , 2018 ). Previous studies reported a tighter KIF11‐association by S‐trityl‐L‐cysteine (STLC) than monastrol (Skoufias et al , 2006 ), and a better pocket‐fitting by ispinesib than monastrol (Zhang et al , 2008a ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the helix a0 and loop L1, a0 and L1 regions of CENP-E have two more residues than that of other kinesins. Although the B factor of these kinesins is below 30 A 2 , the B factors of some residues of CENP-E-MgAMPPNP are over 40 A 2 . We consider that the a0 region and loop L1 of CENP-E-MgAMPPNP are less stable than other kinesins because two residues or more of the longer loop L1 are more flexible.…”
Section: Structural Comparison With Known Structures Of Kinesin-mgamppnpmentioning
confidence: 94%
“…Recently, numerous small‐molecule inhibitors targeting the motor domain of Kinesin‐5, a kinesin essential for mitosis, have been developed for new anticancer agents. Many researchers have elucidated the structures of the inhibitor‐bound Kinesin‐5 motor domain by using X‐ray crystallography, which has helped in rational design of more effective Kinesin‐5 inhibitors [2]. However, inhibitors targeting the Kinesin‐5 motor domain have not been approved for use in clinical practice because of facing with the problem that most inhibitors tested exhibited only limited efficacy [3].…”
mentioning
confidence: 99%